3-O Sulfated Heparan Sulfate (G2) Peptide Ligand Impairs the Infectivity of Chlamydia muridarum - Weronika Hanusiak; Purva Khodke; Jocelyn Mayen; Kennedy Van; Ira Sigar; Balbina J. Plotkin; Amber Kaminski; James Elste; Bajarang Vasant Kumbhar; Vaibhav Tiwari (Biomolecules)
Background: Heparan sulfate (HS) is widely implicated as a receptor for Chlamydia cell attachment and infectivity. However, the enzymatic modification of HS modified by the 3-O sulfotransferase-3 (3-OST-3) enzyme in chlamydial cell entry remains unknown. Methodology: To rule out the possibility that host cell 3-O sulfated heparan sulfate (3-OS HS) plays a significant role in C. muridarum entry, a Chinese hamster ovary (CHO-K1) cell model lacking endogenous 3-OST-3 was used. In addition, we further tested the efficacy of the phage-display-derived cationic peptides recognizing heparan sulfate (G1 peptide) and the moieties of 3-O sulfated heparan sulfate (G2 peptide) against C. muridarum entry using human cervical adenocarcinoma (HeLa 229) and human vaginal epithelial (VK2/E6E7) cell lines. Furthermore, molecular dynamics simulations were conducted to investigate the interactions of the Chlamydia lipid bilayer membrane with the G1 and G2 peptides, focusing on their binding modes and affinities. Results: The converse effect of 3-OST-3 expression in the CHO-K1 cells had no enhancing effect on C. muridarum entry. The G2 peptide significantly (>80%) affected the cell infectivity of the elementary bodies (EBs) at all the tested concentrations, as evident from the reduced fluorescent staining in the number of inclusion bodies. The observed neutralization effect of G2 peptide on C. muridarum entry suggests the possibility of sulfated-like domains being present on the EBs. In addition, data generated from our in silico computational structural modeling indicated that the G2 peptide ligand had significant affinity towards the C. muridarum lipid bilayer. Conclusions: Taken together, our findings show that the pretreatment of C. muridarum with 3-O sulfated heparan sulfate recognizing G2 peptide significantly prevents the entry of EBs into host cells.